2021
DOI: 10.30585/jrems.v3i2.595
|View full text |Cite
|
Sign up to set email alerts
|

Do behavioral, educational, and legal factors determine the applicability of forensic accounting in the public sector?

Abstract: This study examined the impact of educational, legal, and behavioral factors on the applicability of forensic accounting in the public sector in Nigeria. The study utilized primary data through the administration of questionnaires to accountants the internal and external auditors drawn from seven states of the North-Western geo-political zone of Nigeria. Partial Least Squares (PLS) path modeling using smart PLS3 Statistical Software was employed for the analysis. The findings indicated that behavioral, educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Similarly, a sample item for benevolence ethical climate is "It is expected that one will always do what is right for the public". The scale for the measurement of forensic accounting services was adopted from the study of Lawal et al (2021) and modified as to suit our purpose as shown:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a sample item for benevolence ethical climate is "It is expected that one will always do what is right for the public". The scale for the measurement of forensic accounting services was adopted from the study of Lawal et al (2021) and modified as to suit our purpose as shown:…”
Section: Methodsmentioning
confidence: 99%
“…It is a strategic approach for analyzing and minimizing financial crimes and fraud through forensic auditing techniques. However, no matter the level of professional forensic accountants' expertise, they would not achieve the goals of detecting and preventing fraud without the necessary supportive ethical climate (Lawal et al, 2021). Despite the well-researched role of ethical climate on different aspects of firm performance, empirical studies on the effect of ethical climate on the use of forensic accounting services for the detection and prevention of fraud in the public sector are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Big Data has the capacity to forecast future events in addition to analyzing the patterns of past occurrences. Lawal (2021) The need for auditors with Big Data expertise to make business decisions is growing. The authors show that forensic accounting and big data analytics are becoming more and more popular in both practice and education.…”
Section: Sno Author Namementioning
confidence: 99%